Antipodal Vivaldi Array Antenna for LoRa: A Simulation Study within 900–923 MHz Band - Deri Latika Herda; Amelia Yolanda; Gardinia Naz Surya; Uzma Septima; Popy Maria (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
LoRa (Long Range) is a wireless communication technology that has gained significant attention in the Internet of Things (IoT) due to its wide coverage and low power consumption. However, its performance is often affected by environmental obstacles that cause signal attenuation and interference. In Indonesia, LoRa is regulated to operate in the 920–923 MHz band, whereas many commercial devices are designed for 915 MHz, leading to suboptimal antenna performance. Therefore, this research aims to design and simulate an antenna that can operate effectively across 900–923 MHz, covering both the commonly used 915 MHz band and the regulated 920–923 MHz band in Indonesia. The proposed design is a 1×2 Antipodal Vivaldi Array antenna using an FR-4 substrate with a dielectric constant of 4.3 and thickness of 1.6 mm. The simulation process was conducted using CST Studio Suite 2019, focusing on the optimization of key geometric parameters such as feedline width, inter-element spacing, flare structure, and ground plane. The simulated results show that the antenna achieves a return loss of –19.11 dB at 923 MHz, a bandwidth of 344.4 MHz, and a gain ranging from 5.103 dBi at 900 MHz to 5.162 dBi at 923 MHz. The radiation pattern is directional, which supports long-range communication requirements. These findings demonstrate that the proposed antenna design meets the specifications for LoRa communication and provides a wideband, directional solution that can enhance the reliability of IoT systems.